The Effect of Increasing Tibial Tuberosity Advancement and Quadriceps Muscle Force on Cranial Translation of the Tibia in the Cranial Cruciate Deficient Stifle Joint in Dogs - Ober, Ciprian; Berger, Chen; Cohen, Liat; Milgram, Joshua (Frontiers in Veterinary Science, 2022)
Background: Cranial cruciate ligament (CCL) disease is a well-known pathology which generates both rotational and translational instability of the stifle joint that leads to the osteoarthritis in dogs. Tibial tuberosity advancement (TTA) is a common surgical technique used to dynamically neutralize the tibiofemoral shear forces to achieve stifle joint stability. Significant instability persists in treated cases according to many suggestions. The purpose of this study was to evaluate the effect of increasing quadriceps load, increasing tibial tuberosity advancement, and increasing joint flexion angle on cranial translation of the tibia relative to the femur in the cranial cruciate ligament deficient stifle joint. Methods and Results: Six cadaveric hind limbs were collected from 6 healthy mixed breed dogs of medium build and prepared for biomechanical testing. The specimen was placed into a custom-made joint testing machine, and translation of the tibia relative to the femur was measured at stifle angles of 135º, 120º, and 105º. Cranial tibial thrust was generated by applying a vertical load to the metatarsal pad and the quadriceps muscle was simulated with loads of 0 kg, 5kg, and 10 kg applied to the patella via a system of weights and pulleys. All specimens were tested with the CCL intact and cut, both of which served as controls. The tibial tuberosity was then advanced using both 6 mm and 9 mm cages, and the specimen was tested using the identical technique. Each specimen was loaded to failure by increasing the load applied to the pes until sudden marked cranial translation of the tibia. Tibial tuberosity advancement with an applied quadriceps load was successful in limiting cranial tibial translation in 54/62 tests. Under similar loading conditions TTA failed to limit cranial translation in 8 tests. The failures occurred at all angles of flexion examined. In the cases that failed cranial translation could be limited by either increasing the quadriceps load or increasing the amount of tibial tuberosity advancement. Conclusion: This study showed that TTA with an applied quadriceps load is effective at decreasing cranial tibial translation at functional joint angles.